2022
DOI: 10.1021/acsapm.2c01694
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mechanical Properties of Poly(butylene adipate-co-terephthalate)/Cellulose Nanocrystal Nanocomposites Obtained by In Situ Polymerization

Abstract: Biodegradable plastic films, in which poly(butylene adipate-co-terephthalate) (PBAT) is a major component, play a significant role in the expansion of the sustainable plastic packaging market. Unfortunately, biodegradable films tear easily. To garner consumer attention, it is paramount that these materials not only offer sustainability benefits but also provide durability. To enhance the mechanical properties of PBAT, an in situ method that polymerizes monomers upon the addition of aqueous cellulose nanocrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…This material is a biodegradable polymer, and could be derived from sustainable resources. 4 A high number of flexible aliphatic chains of PBAT in its macromolecular chain, lead to the material with good tensile properties, flexibility, ductility, and fracture toughness, also excellent processability, and adjustable biodegradability; 5,6 However, a slower crystallization rate, a lower degree of crystallinity, and modulus of elasticity are crucial issues that severely hinder its application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This material is a biodegradable polymer, and could be derived from sustainable resources. 4 A high number of flexible aliphatic chains of PBAT in its macromolecular chain, lead to the material with good tensile properties, flexibility, ductility, and fracture toughness, also excellent processability, and adjustable biodegradability; 5,6 However, a slower crystallization rate, a lower degree of crystallinity, and modulus of elasticity are crucial issues that severely hinder its application.…”
Section: Introductionmentioning
confidence: 99%
“…The depletion of petrochemical resources has led researchers to the development of biobased polymer materials derived from sustainable resources. PBAT is the main alternative material for petroleum-based plastics like polyethylene and polypropylene. This material is a biodegradable polymer, and could be derived from sustainable resources . A high number of flexible aliphatic chains of PBAT in its macromolecular chain, lead to the material with good tensile properties, flexibility, ductility, and fracture toughness, also excellent processability, and adjustable biodegradability; , However, a slower crystallization rate, a lower degree of crystallinity, and modulus of elasticity are crucial issues that severely hinder its application.…”
Section: Introductionmentioning
confidence: 99%
“…27 Meanwhile, Kim et al claimed that the insitu polymerization of PBAT/CNC nanocomposites exhibited an outstanding reinforcing effect even at minimal filler content (0.05 wt%). 28 In this study, we prepared biodegradable nanocomposite fibers composed of PBAT and CNC with remarkable mechanical strength and toughness using dry-jet wet spinning. PBAT and CNC were mixed well in DMSO as a common solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammadi et al found that a binary solvent mixture of tetrahydrofuran and dimethyl sulfoxide (DMSO) was suitable for preparing PBAT/CNC nanocomposites 27 . Meanwhile, Kim et al claimed that the in‐situ polymerization of PBAT/CNC nanocomposites exhibited an outstanding reinforcing effect even at minimal filler content (0.05 wt%) 28 …”
Section: Introductionmentioning
confidence: 99%